Optimizing Control Strategies for Hand Exoskeleton: A Comparative Study of Controllers - Jamaludin Jalani; Ab Aziz, Ab Wafi; Sadun, Amirul Syafiq (International Journal of Integrated Engineering, 2025)
This study presents a comparative analysis of three controllers (PI, Fuzzy Logic Control, and Sliding Mode Control) for hand exoskeletons designed for stroke patients. The research evaluates the controllers' performance in manipulating the exoskeleton to specific target angles, with results indicating competitive performance across various data metrics. The methodology involves the design and simulation of each controller using Matlab Simulink software, with the hand exoskeleton featuring a unique four-finger rigid design and an Actuonix linear motor. Notably, the study identifies Sliding Mode Control as the most effective controller, demonstrating superior stability, accuracy, minimal overshoot, zero steady-state error, and the fastest settling time. This research significantly advances hand exoskeleton technology for individuals with hand impairments. The study offers valuable insights for the development and implementation of control systems in hand exoskeleton technology, with implications for assistive applications.